Maryja – „doskonała ikona wiary” Wokół autorstwa maryjnego wątku encykliki Lumen fidei - Wojtczak, Adam (Poznańskie Studia Teologiczne, 2016)
The article addresses two main questions: What image of Mary’s faith does the encyclical Lumen fidei portray? What fruits does the encounter of Mary’s faith and the faith of the Church bring out? The subtitle suggests one more issue: since the encyclical was written by two Popes, (Benedict XVI and Francis), it is interesting to try to determine who wrote particular themes on the topic of Mary's faith. The first chapter presents Mary, the Daughter of Zion, who fulfilled the faith of Israel, and also initiated the faith of the Church. The second chapter characterizes the relation of Mary to the Word of God, which she listened to, kept in her heart and unconditionally accepted in order to live in total harmony with God. The third chapter concerns Mary's journey of faith at Jesus’s side, which was marked with the joy of the Annunciation, as well as with the Cross, finally reaching its destination in the light of his resurrection. The last chapter focuses on the reference of Mary's faith to the faith of the Church. In Mary's school, we learn to trust God and his word, to focus on Jesus, to contemplate him, to follow him, to perceive with his eyes, to cherish his feelings, and to adopt his attitudes. Only such faith brings fruits and joy. The encyclical teaching on Mary’s faith, as read in the context of other statements from both Popes, enables us to establish the following: 1. From Benedict XVI comes the Lumen fidei teaching on Mary, the Daughter of Zion, a woman who accepts and lives by the Word of God; the emphasis on Mary as a model of faith; and the motto “those who believe are never alone”. 2. Francis can be credited with the themes concerning the impact of Mary’s faith on our lives, both personal and social; learning from her how to see with the eyes of Jesus; and entrusting ourselves to his love. He calls her the Mother of our faith to emphasize her maternal care over the faith of the Church.